Breast milk and its impact on maturation of the neonatal immune system. Issue 3 (June 2015) - Turfkruyer, Mathilde; Verhasselt, Valerie
Abstract : Purpose of review: This article aims to review the evidence that breast milk can actively shape neonate gut immune system development toward a mature immune system capable of responding appropriately to encountered antigens. Recent findings: Recent findings in the adult have demonstrated the critical role of the interaction between diet, gut microbiota, gut epithelial cells and gut-associated lymphoid tissue in the development of immune responses. Here, we will review what is known in this field in the neonate, compare these data to those obtained in the adult and review how milk factors impact gut immune function in the short and long term. Summary: We propose that the neonate immune system and maternal milk represent an entity necessary to ensure not only appropriate function in early life but also long term immune homeostasis.